Italian grammar for dummies - Bartolini-Salimbeni, Beth (Hoboken, NJ : John Wiley & Sons, Inc., 2013)
A hands-on guide to mastering the written aspects of Italian.
Includes index.
Text is in English and Italian.
Keywords: Italian language -- Grammar; Italian language -- Textbooks for foreign speakers -- English